2013
DOI: 10.1038/ncb2765
|View full text |Cite
|
Sign up to set email alerts
|

Sequential introduction of reprogramming factors reveals a time-sensitive requirement for individual factors and a sequential EMT–MET mechanism for optimal reprogramming

Abstract: Present practices for reprogramming somatic cells to induced pluripotent stem cells involve simultaneous introduction of reprogramming factors. Here we report that a sequential introduction protocol (Oct4-Klf4 first, then c-Myc and finally Sox2) outperforms the simultaneous one. Surprisingly, the sequential protocol activates an early epithelial-to-mesenchymal transition (EMT) as indicated by the upregulation of Slug and N-cadherin followed by a delayed mesenchymal-to-epithelial transition (MET). An early EMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
183
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(215 citation statements)
references
References 50 publications
17
183
2
2
Order By: Relevance
“…135 It was recently shown that optimal reprogramming to stem cells was obtained by step-wise introduction of the factors listed above and involved a sequential EMT-MET process. 133 Data from other research groups also confirm the reprogramming to iPSCs as a multistep process, where pluripotency during the early EMT phase is promoted by TGFb. In the later MET phase, BMP signaling plays a key role by upregulating miR-200 family members that enforce the epithelial phenotype.…”
Section: Emt and Breast Cancer Stem Cellsmentioning
confidence: 53%
“…135 It was recently shown that optimal reprogramming to stem cells was obtained by step-wise introduction of the factors listed above and involved a sequential EMT-MET process. 133 Data from other research groups also confirm the reprogramming to iPSCs as a multistep process, where pluripotency during the early EMT phase is promoted by TGFb. In the later MET phase, BMP signaling plays a key role by upregulating miR-200 family members that enforce the epithelial phenotype.…”
Section: Emt and Breast Cancer Stem Cellsmentioning
confidence: 53%
“…Mechanistically, Sox2 suppresses expression of Snail, an EMT inducer [48] , and Klf4 induces E-cadherin expression, thus promoting MET [41] . In addition, Maekawa et al [49] have shown that the Glis family zinc finger 1 protein Glis1 can substitute cMyc in the reprogramming cocktail by inducing MET, thus initiating iPS cell reprogramming.…”
Section: Initiationmentioning
confidence: 99%
“…To practically group cells into the M-and E-Grand divisions, we could take advantage of the ratio of E-cadherin (epithelial) to N-cadherin (mesenchymal) as it was successfully utilized to predict reprogramming potentials of various cells [2]. To extend this logic further, we have performed a metaanalysis on the gene expression profiles of 745 human primary cell samples from BioGPS (http://biogps.org, dataset Primary Cell Atlas) and found that ~25% of all cell types are high in N-cadherin (mesenchymal) and ~55% of cell types are high in E-cadherin (epithelial).…”
mentioning
confidence: 99%